Fra pessimisme til sosialistisk realisme. Symfonikeren Nikolaj Mjaskovskij (1881–1950). Del 2 - Asbjørn Ø. Eriksen (Studia Musicologica Norvegica)
Abstract Nikolay Myaskovsky (1881–1950) was highly esteemed as a Soviet composer, only surpassed by Prokofiev and Shostakovich among his contemporaries, and in the West famous conductors like Stokowski and Furtwängler performed his symphonies. Interest in Myaskovsky’s music waned after his death, but thanks to recordings of all his twenty-seven symphonies and to his first extensive biography in English (2014), new listeners have become aware of this composer. The author offers a consideration of Myaskovsky’s development as a symphonist, focusing on style and sources of influence, and the way his symphonies reflect the ideological climate in the Soviet Union in the 1920s and during the Stalinist regime. The composer reached a peak in his symphonic oeuvre with his monumental Sixth Symphony (1921–23), which reflects the suffering of the Russian people as a consequence of the Russian Revolution. While Myaskovsky tried out different formal solutions and styles in his symphonies dating from the 1920s, he tried to satisfy the doctrine of Socialist realism in symphony numbers 14 to 27 (1933–49), and the idiom becomes quite retrospective, harking back to the style of Russian composers from the nineteenth century. Myaskovsky’s music lacks the irony and grotesque humour that distinguish several of Prokofiev’s and Shostakovich’s works, but at his best he grips us with a focused and distinctive voice.